Building social capital in networks - Batt, Peter (Elsevier Publisher, 2008)
This paper explores the re-emerging concept of social capital in business networks. Spanning a multitude of disciplines and different contexts, the construct remains ill defined and its measurement imprecise, yet researchers in both the developed and transitional economies are increasingly finding it necessary to draw upon social capital as a means of explaining behavior within embedded social networks. We encourage and indeed implore researchers to continue to explore the construct and its impact on the performance of business networks.